(untitled) (Proceedings of the International Conference on Public Health, 2017)
Ageing being the most emerging demographic phenomenon in the world today, there is an increase in demand for preventive, curative care and rehabilitation services. With the population rising in India, the elderly population is likely to accelerate further in the coming years and therefore there is a need to know the quality of life of elderly and develop mixed strategies to meet their health care needs. Of the total population in Sikkim, around 75.03 % live in the rural areas. With 6.7% of the elderly population in the state,the objective of this study was to find out the quality of life of geriatric population in rural areas of East Sikkim.A cross-sectional study was carried out by visiting the Gram Panchayat Units(GPU’s), where elderly people were randomly selected from 18 GPUs out of 53 GPU’s in rural areas of east Sikkim. Study included 324 elderly people with age more than or equal to 60 years.World Health Organisation Quality of Life BREF (WHOQOL-BREF) questionnaire was used for assessing the quality of life. Physical health, psychological, social relationships and environmental quality of life in both genders were found to be poor (Mean 39.5±11.26 SD). There was no significant difference between gender and age variables in quality of life. Quality of life is found to be poor in the geriatric population of Sikkim due to the environmental barrier, reduced psychological, social relationships and physical health. Further studies are required to study the overall quality of life of elderly to promote graceful ageing through comprehensive geriatric care